1997
DOI: 10.1042/bj3210139
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between ATP, oleandomycin and the OleB ATP-binding cassette transporter of Streptomyces antibioticus involved in oleandomycin secretion

Abstract: The OleB protein of Streptomyces antibioticus, oleandomycin (OM) producer, constitutes an ATP-binding cassette transporter containing two nucleotide-binding domains and is involved in OM resistance and its secretion in this producer strain. We have characterized some properties of the first nucleotide-binding domain of OleB using an overexpressed fusion protein (MBP-OleB') between a maltose-binding protein (MBP) and the first half of OleB (OleB'). Extrinsic fluorescence of the base-modified fluorescent nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…It has been reported that either one of the two ABC domains of Ole(B) is sufficient to confer resistance to oleandomycin (30). Moreover, it was demonstrated that the N-terminal ABC domain of Ole(B) is able to recognize oleandomycin (8). To test the possibility that each ABC domain of Vga(A) would behave similarly in conferring resistance to SGA, we constructed truncated versions of vga(A) by subcloning each half of the gene on separate plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that either one of the two ABC domains of Ole(B) is sufficient to confer resistance to oleandomycin (30). Moreover, it was demonstrated that the N-terminal ABC domain of Ole(B) is able to recognize oleandomycin (8). To test the possibility that each ABC domain of Vga(A) would behave similarly in conferring resistance to SGA, we constructed truncated versions of vga(A) by subcloning each half of the gene on separate plasmids.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins of this subfamily are involved in MLS antibiotic resistance. To the best of our knowledge, only a fragment of Ole(B), a protein belonging to this subfamily, has been produced and purified successfully (24). However, this construct consisted of a fusion of the E. coli maltose-binding protein to the N-terminal ABC domain of Ole(B).…”
Section: Discussionmentioning
confidence: 99%
“…Many ARE subfamily proteins were found in MLS antibiotic-producing actinomycetes (23). The most studied ARE proteins are Ole(B), from the oleandomycin producer Streptomyces antibioticus (24), and two proteins of distinct specificities: Msr(A) and Vga(A), both of which are coded by mobile genetic elements in staphylococci. Msr(A) confers a high level resistance to 14-and 15-membered ring macrolides and to SgB components (25), whereas Vga(A) confers a low level resistance to lincosamides and a high level resistance to SgA components (14).…”
mentioning
confidence: 99%
“…Binding of oleandomycin to a maltose-BP-OleB fusion protein was detected by intrinsic fluorescence (56), but the apparent affinity for the antibiotic was low, in the millimolar range, and no saturation of the signal was reached due to competing absorbance of the compound itself. Given that no interacting TM domains have been identified in this family, substrate specificity may be determined by the ABC proteins.…”
Section: Art Family Of Proteins With Diverse Functionsmentioning
confidence: 99%